Performance differences between 26 and 29-inch wheels in cross-country mountain biking - Moreno-Manas, E.; Garcia-Masso, X.; Llana-Belloch, S. (International Journal of Performance Analysis in Sport, 2023)
The popularity of 29-inch mountain bike wheels for cross-country races has been increasing since 2010, but scientific studies supporting their benefits are very scarce. The aim of this study was to analyse the effect of the different bicycle version (i.e. 26 vs 29-inch) in terrain with varying inclinations. Our results indicated that for full laps, the 29" version was slightly faster than 26" version (15.92 vs. 15.74 km/h; p < .001). No differences in the power outputs for these two conditions were reported (p > .05), but a higher mean heart rate (p = .009) was obtained for the riders using the bike with the 29" wheels (167.84 vs. 167.19 bpm; p < .015). Similar results were obtained for the uphill and flat sections, however, there were no differences (p > .05) between the bikes during the downhill sections for any of the studied variables. In conclusion, the 29" version performed better on the flat or uphill terrain but their use also resulted in increased rider heart rates compared to those using the 26"-inch version; no differences were reported for the downhill terrain. This information is relevant to MTB cyclists and could help them to improve their performance.